Traditional textile of Kain Punca Potong design identity - Ahmad, Nani Hartina; Shaari, Nazlina; Mohd Ali, Noor Azizi; Abd Latif, Muhammad Pauzi (Universiti Teknologi MARA, Perak Branch, Tapah Campus, 2019)
Kain Punca Potong (KPP) is a Malay traditional textile is derived from a combination of creative patterns, design, motifs and the value of gold within a community. All these factors determine their commercial and aesthetic value of creating a design characteristic identity in the context of the multi-ethnic and cultural. Generally, there is no evidence that the characteristics of KPP design identity can be generalized based on the production process. The purpose of this research is to develop a conceptual framework based on the literature review in identifying the design identity of KPP to use on creativity and motif that represents Kelantan’s weaving. A conceptual framework for identifying the design identity of KPP is important to preserving the Malay traditional fabrics. The content analysis and KJ methods will be used to build the conceptual framework in establishing a design concept. A literature review has been carried out to identify the existing frameworks related to design and motif selection and implementation of pattern characteristic in KPP for the weaving industry. The findings (or results) of the work should be formulated to support the conceptual framework and this research will provide the overall aesthetic of design identity of KPP.